REFRAMING ISLAMIC VALUES IN EDUCATION MANAGEMENT: EVALUATING THE MERDEKA CURRICULUM THROUGH AN ISLAMIC LEADERSHIP LENS - Utami Maulida; Jaenal Arifin; Siti Murtiningsih (Indonesian Journal of Education (INJOE), 2025)
The transformation of education in Indonesia through the Independent Curriculum emphasizes flexibility, differentiatory learning, and character strengthening. However, its implementation in Islamic educational institutions requires a more in-depth study of how Islamic values are represented and integrated in learning practices. This research aims to evaluate the Independent Curriculum from the perspective of Islamic leadership and offer a framework for reframing Islamic values in education management. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis in schools and madrassas that implemented the Independent Curriculum. Thematic analysis reveals that the integration of Islamic values, such as amanah, adl, ikhtiyar, and ihsan, remains partial and highly dependent on teachers' initiative and the school leadership culture. The findings also confirm that leaders who practice Islamic leadership principles are able to create a more ethical, collaborative, and character-oriented learning culture. This research proposes a model of integrating Islamic values at three levels: curriculum, learning practices, and school leadership. Overall, this study highlights the importance of harmonizing national curriculum policies with Islamic values, as well as the need for more systematic guidelines to support the implementation of the Independent Curriculum in the Islamic education context.